Synthesis, Characterization and Biological Activity Evaluation of Some Pyrazoles, Thiazoles and Oxazoles Derived from 2-Mercaptoaniline - Ahmood Kh. Jebur AL-Joubory; Layth W. Abdullah; Abdullah Jasim Mohammed (مجلة بغداد للعلوم, 2021)
Synthesis of 2-mercaptobenzothiazole (A1) is performed from the reaction of  o-aminothiophenol and carbon disulfide CS2 in ethanol under basic condition. Compound (A1)  is reacted with chloro acetyl chloride to give compound (A2). Hydrazide acid compound (A3) is obtained from the reaction of compound (A2) with  hydrazine hydrate in ethanol under reflux in the presence of glacial acetic acid .The reaction of hydrazide acid compound (A3) with ethyl acetoacetate gives pyrazole compound (A4). The new hydrazone  compound (A5) was prepared from the reaction of compound (A3) with  benzaldehyde. Reaction of compound (A3) with  thiourea  dissolved in ethanol  gave  2-amino thiazole  compounds(A6) which was used the reaction with 4–N,N-dimethyl benzaldehyde to yield  compound hydrazone (A7).While, the reaction of compound (A2) with  urea  in the presence of ethanol  gave 2-amino oxazole  compounds (A8) which was used in the reaction with 3-hydroxy – 4 -methoxy benzaldehyde to yield hydrazone (A9). The structures of the prepared compounds were established by spectral (1H-NMR,Elemental analysis (C.H.N- ),and  FT-IR. In addition to systematic characterization of some active functional groups in these compounds, antibacterial activity (Esheriechia coli,  Bacillus subtilis ) for some of the synthesized compounds were evaluated against two types of fugal (Candida albicans ) , the synthesized compounds.